Community Capacity: A Concept Analysis - Asri, Asri; Husna, Anis Rosyiatul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2017)
Objective: The purpose of this analysis is to clarify the concept of community capacity by using Walker and Avant's (1995) concept analysis.Methods: This article based on identification of the concept from various resources included: dictionary, articles, case study. Results: Community capacity was the process or activities which use systematic approach which involve the competence and ability of the community in dealing with and solving the problem and raise into the welfare state of being in multi-sectoral way .